Regulation of subcellular distribution of GLUT4 in cardiomyocytes: Rab4A reduces basal glucose transport and augments insulin responsiveness - Dransfeld, O.; Uphues, I.; Sasson, S.; Schürmann, A.; Joost, H.-G.; Eckel, J. (Experimental and Clinical Endocrinology & Diabetes, 2000)
Members of the Rab subfamily of small-GTP binding proteins have been suggested to be involved in insulin-regulated translocation of the glucose transporter GLUT4. To directly study this process in muscle tissue, we have established an insulin-sensitive cardiac cell line (H9K6) stably overexpressing GLUT4, which was derived from H9c2 cardiac myoblasts. H9K6-cells were transiently transfected with rab4A and rab3C with an efficiency of 65% and glucose uptake and the cellular distribution and expression of the transporter isoforms GLUT1 and GLUT4 was subsequently determined. Rab3C-overexpression caused no significant change in both basal and insulin-stimulated 2-deoxyglucose uptake compared to control cells transfected with the blank vector. Rab4A was barely detectable in membranes of H9K6 cells. However, after transient transfection this protein was expressed at a level comparable to adult cardiomyocytes. This resulted in a reduction of basal glucose uptake by 31% compared to control cells. Under these conditions insulin was able to stimulate 2-deoxyglucose uptake by 120%. Total expression of GLUT1 and GLUT4 was not affected by Rab4-overexpression. Cell surface biotinylation was used to quantify the abundance of GLUT1 and GLUT4 in the plasma membrane. A decrease of cell surface GLUT4 by about 40% compared to control cells was found in Rab4-overexpressing cells. Insulin treatment increased cell surface-GLUT4 by 100% compared to only 26% in control cells. Distribution of GLUT1 was not affected under these conditions. Our data show that Rab4A but not Rab3C is able to reduce basal glucose uptake and cell surface content of GLUT4 in cardiac muscle cells. This results in an increased stimulation of glucose uptake by insulin which can be fully explained by enhanced translocation of GLUT4. We suggest that Rab4A participates in the redistribution of GLUT4 to intracellular pools and represents an essential determinant of the insulin responsiveness of GLUT4 translocation in cardiac muscle cells.
Keywords: GLUT4; Rab4A; cardiomyocytes; glucose transport